Pendalaman Ilmu Nahwu dengan Metode Diskusi di Asrama Darus Shibyan - Mannan, Ahmad Mizan Rosyadi Abdul Jalil; Nadhir, Muhammad Mundhir (INAIFAS Press, 2023)
Deepening the science of Nahwu is very urgent, because Nahwu science is a tool science that must be mastered before studying other sciences. The application of the discussion method is very effective for the marhalah ibtidaiyah students in the Darus Shibyan dormitory who in fact still find it difficult to understand the basics of Nahwu. The aim of this research is to assist the students of the Darus Shibyan dormitory to be more in-depth and critical in the Nahwu science lessons, so that they can understand Arabic. The methods used are community development and discussion practice. The data collection technique uses observation and documentation. As a result of this research, the students of the Darus Shibyan boarding school were able to understand the basic Nahwu rules, and were able to describe I'rab and its position. This identifies that the discussion method is an alternative step to deepen Nahwu knowledge.